2022
DOI: 10.47191/ijmra/v5-i5-15
|View full text |Cite
|
Sign up to set email alerts
|

ICT Skills, E-Supervision Scheme of School Heads, And Teacher Development in Distance Learning Among Selected Private Schools in Cainta

Abstract: The study aimed at examining the interplay the relationship among the ICT skills, e-supervision scheme of school heads, and teacher development in distance learning which longed to be a valuable undertaking in the time of pandemic where alternative delivery mode of education is implemented; skills of school heads in Information and Communication Technology (ICT) have been challenged and brought impact to their administrative and academic role. Descriptive-correlational design was employed. The study revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the Philippines, teacher supervision is considered important for better teaching and learning. Thus, Ruel and Bautista (2022) conducted a study to investigate the interplay of the relationships between ICT skills, e-supervision schemes of school heads, and teacher development in distance learning, which they hoped would be a valuable undertaking during a pandemic where alternative delivery modes of education were implemented. The study revealed that school heads had very high ICT skill levels in terms of utilization and competence, very high e-supervision scheme levels in terms of video conferencing, instant messaging, and the office suite, and a very high level of teacher development in distance learning.…”
Section: Headteachers' Supervisory Strategies and Teachers' Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the Philippines, teacher supervision is considered important for better teaching and learning. Thus, Ruel and Bautista (2022) conducted a study to investigate the interplay of the relationships between ICT skills, e-supervision schemes of school heads, and teacher development in distance learning, which they hoped would be a valuable undertaking during a pandemic where alternative delivery modes of education were implemented. The study revealed that school heads had very high ICT skill levels in terms of utilization and competence, very high e-supervision scheme levels in terms of video conferencing, instant messaging, and the office suite, and a very high level of teacher development in distance learning.…”
Section: Headteachers' Supervisory Strategies and Teachers' Performancementioning
confidence: 99%
“…Thus, the headteachers who provide clear guidance and support to teachers in understanding the CBC framework, its objectives, and the expected outcomes can significantly enhance teachers' confidence and motivation and improve their performance in the implementation of the curriculum. As Ruel and Bautista (2022) noted, headteachers play a crucial role in monitoring classroom activities, which allows them to assess how well CBC is being implemented. Constructive feedback from headteachers helps teachers identify areas for improvement and make necessary adjustments to their teaching strategies, which consequently improves their performance.…”
Section: Headteachers' Supervisory Strategies and Teachers' Performancementioning
confidence: 99%